Changes in the Sensitivity to Language-Specific Orthographic Patterns With Age - Duñabeitia, Jon Andoni; Borragán, María; de Bruin, Angela; Casaponsa, Aina (Frontiers in Psychology, 2020)
How do bilingual readers of languages that have similar scripts identify a language switch? Recent behavioral and electroencephalographic results suggest that they rely on orthotactic cues to recognize the language of the words they read in ambiguous contexts. Previous research has shown that marked words with language-specific letter sequences (i.e., letter sequences that are illegal in one of the two languages) are recognized more easily and faster than unmarked words. The aim of this study was to investigate sensitivity to markedness throughout childhood and early adulthood by using a speeded language decision task with words and pseudowords. A large group of Spanish-Basque bilinguals of different ages (children, preteenagers, teenagers and adults) was tested. Results showed a markedness effect in the second language across all age groups that changed with age. However, sensitivity to markedness in the native language was negligible. We conclude that sensitivity to orthotactics does not follow parallel developmental trend in the first and second language.